Nutrient digestibility on ruminal fermentation in vitro with addition of rumen modifier based on Clove (Syzygium aromaticum. L.) and Fennel (Foeniculum vulgare. Mill.) Essential Oil - Kurniawati, Asih; Saputra, Wahyu Eka; Mahardillah, Latifah; Hanim, Chusnul; Yusiati, Lies Mira (2019)
Effect of rumen modifier (RM) with clove or fennel essential oilon nutrient digestibility was studied in in vitro batch fermentation. RMs were mix with feed materialto meet concentration of 0, 25, 50, 75 and 100 μl/l of medium. Feed consist of forage, wheat pollard and rice bran (60:20:20DM based). In vitro gas production technique was used with Ongole grade cattle as rumen microbe donor. Fermentation was done at 39°C. Residuals feed were collected after 24 hours of incubationfor nutrient content analysis as data for calculation of dry matter (DMD), organic matter (OMD), crude protein (CPD) and crude fibre (CPD) digestibility. RMs reduced DMD and OMD (P<0.01) start at clove RM of 25 μl/l whereas fennel RM at 50 μl/l. Range of DMD and OMD value were 30.17 to 43.55% and 35.53 to 47.98% respectively. CPD reduced byclove RM(P<0.05) otherwise did not affected by fennel RM. CPDdecreased at clove RM 50 μl/l and gradually decline with increasing of RM. RM increased CFD (P<0.01), but at 100 μl/l CFD was not significant differentfrom control. In conclusion, fennel essential oil have lesser negative effect on nutrient digestibility as RM at doses 25 to 50 μl/l.